Analysis of the Effect of Profitability and Effective Tax Rate on Capital Structure with Conservatism as a Moderating Variable - Ningtiyas, Annisa Lufi; Subowo, S (Accounting Analysis Journal, 2019)
This study aims to investigate the effect of profitability and effective tax rate on capital structure with accounting conservatism as a moderating variable. The population are companies listing on Indonesia Stock Exchange in the last 5 years after the global crisis in 2008 that is 2014-2016 with 115 companies. The research sample was selected using purposive sampling technique. Based on the criteria, there are 67 samples with 201 units of analysis. Data were analyzed using moderate regression with SPSS 21. The results indicated that profitability has a negative effect on the capital structure. In contrast, effective tax rate has a positive effect on the capital structure. Accounting conservatism is a kind of pseudo-moderation that has a positive influence on the capital structure. However, as a moderating variable accounting conservatism is only able to moderate the effect of effective tax rate on capital structure. The results indicated that accounting conservatism significantly weakens the effect of effective tax rates on the capital structure. Based on the results, it can be concluded that the capital structure is influenced by profitability, effective tax rate, accounting conservatism, and the effect of effective tax rate on capital structure moderated by accounting conservatism.